2019
DOI: 10.1021/acs.macromol.9b00772
|View full text |Cite
|
Sign up to set email alerts
|

Roll-to-Roll Scalable Production of Ordered Microdomains through Nonvolatile Additive Solvent Annealing of Block Copolymers

Abstract: A new method, “nonvolatile solvent vapor annealing” (NVASA), has been developed to anneal block copolymers during film deposition by controlling the solvent drying process. Precise amounts of high boiling point additive added to the polymer solution briefly remain in the polymer film after casting, leaving the film in a swollen state, increasing its chain mobility, and ultimately improving domain order. We demonstrated the effectiveness of NVASA on several block copolymer systems and used in situ grazing incid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…Analogous to the constant-swelling-ratio SVA study reported by Gu et al, 58 such experiments may, in principle, be performed by exercising precise control over the solvent pressure above the swollen film, 35 or by retention of nonvolatile plasticizer as proposed by Weller and co-workers. 72 ■ CONCLUSIONS Overall, our straightforward, single-step solvent evaporation annealing protocol is a viable alternative to more complex block-copolymer directed self-assembly methods. Due to its simplicity and compatibility with various film-casting techniques, the method is easy to implement in any soft-matter research laboratory, enabling rapid BCP patterning on various substrates without the need for specialized processing instrumentation.…”
Section: ■ Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Analogous to the constant-swelling-ratio SVA study reported by Gu et al, 58 such experiments may, in principle, be performed by exercising precise control over the solvent pressure above the swollen film, 35 or by retention of nonvolatile plasticizer as proposed by Weller and co-workers. 72 ■ CONCLUSIONS Overall, our straightforward, single-step solvent evaporation annealing protocol is a viable alternative to more complex block-copolymer directed self-assembly methods. Due to its simplicity and compatibility with various film-casting techniques, the method is easy to implement in any soft-matter research laboratory, enabling rapid BCP patterning on various substrates without the need for specialized processing instrumentation.…”
Section: ■ Resultsmentioning
confidence: 97%
“…Analogous to the constant-swelling-ratio SVA study reported by Gu et al, 58 such experiments may, in principle, be performed by exercising precise control over the solvent pressure above the swollen film, 35 or by retention of nonvolatile plasticizer as proposed by Weller and co-workers. 72 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[525] The narrow pore size distribution of these BCP-derived membranes provides advantages of high selectivity and high pore densities for enabling a high flux. [526] Therefore, nearly one order of magnitude increase in water permeability can be achieved by using isoporous BCP membranes for ultrafiltration applications compared to commercial membranes with similar pore sizes. [527] For these filtration relevant applications, development of perpendicularly aligned domains throughout the entire film thickness is essential.…”
Section: Filtration Membranesmentioning
confidence: 99%